Characterization of biotic and sodic lawns of the Kruger National Park using the framework of the positive feedback loop / Courtney Moxley - Moxley, Courtney (Department of Biological Sciences, 2015)
The classical grazing lawn model is an intensely-grazed patch composed of short-statured, grazing-tolerant grass species. The formation and maintenance of these communities is controlled by positive feedbacks between grazers and the high-quality resource forage that the component grass species provide. Different nutrient cycling dynamics among the lawns identifies two discrete lawn types in the savanna: bioticallydriven lawns on nutrient-rich gabbroic soils and abiotically-driven lawns at sodic sites. We were interested in identifying whether the biotic and sodic lawns represented two distinct systems in terms of the feedback responses among herbivores, decomposers and grass and decomposer community assemblages in a mesic savanna. We sampled these components of the abiotic and biotic template of five sodic and five biotic lawns in the Kruger National Park. We used Î² diversity in grass and dung beetle community assemblages among the lawns to identify whether sodic and biotic lawns were distinct for grass percent cover and dung beetle species abundance. Four and three categories of lawns were identified for these traits, respectively, and placed the lawns on a gradient from biotic-like to sodic-like with a range of intermediates. Soil Na content was higher among sodic lawns but these levels did not manifest themselves in the grass foliar Na content, as for biotic lawns. Herbivore utilization of the sodic lawns was higher than the biotic lawns. Biotic lawns showed no difference in herbivore metabolic biomass between the late-wet and early-mid dry season. We concluded that the systems of nutrient cycling and lawn maintenance are distinct between the biotic and sodic lawns, but that the lawns exist along a gradient in terms of their community characteristics and abiotic features. Efforts to classify grazing lawns will present benefits in improving our understanding of their dynamics and, resultantly, the management and conservation approaches that use them to control herbivore populations in African savanna ecosystems.